2014
DOI: 10.1038/srep06782
|View full text |Cite
|
Sign up to set email alerts
|

Self-recognition in corals facilitates deep-sea habitat engineering

Abstract: The ability of coral reefs to engineer complex three-dimensional habitats is central to their success and the rich biodiversity they support. In tropical reefs, encrusting coralline algae bind together substrates and dead coral framework to make continuous reef structures, but beyond the photic zone, the cold-water coral Lophelia pertusa also forms large biogenic reefs, facilitated by skeletal fusion. Skeletal fusion in tropical corals can occur in closely related or juvenile individuals as a result of non-agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…This hypothesis is generally consistent with empirical observations of biogenic calcium carbonates, in which ν 1 peak widths increase as ambient seawater pCO 2 decreases and/or pH increases (i.e. higher Ar ) (Kamenos et al, 2013;Hennige et al, 2015;Pauly et al, 2015). However, corals exert strong control on the carbonate chemistry of their calcifying fluid by elevating pH and/or Ar at the site of calcification to facilitate more rapid crystal growth (Al-Horani et al, 2003;Venn et al, 2011;McCulloch et al, 2012).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This hypothesis is generally consistent with empirical observations of biogenic calcium carbonates, in which ν 1 peak widths increase as ambient seawater pCO 2 decreases and/or pH increases (i.e. higher Ar ) (Kamenos et al, 2013;Hennige et al, 2015;Pauly et al, 2015). However, corals exert strong control on the carbonate chemistry of their calcifying fluid by elevating pH and/or Ar at the site of calcification to facilitate more rapid crystal growth (Al-Horani et al, 2003;Venn et al, 2011;McCulloch et al, 2012).…”
supporting
confidence: 87%
“…In biogenic calcium carbonates, correlations have been reported between ν 1 peak widths and environmental conditions, including temperature and seawater pCO 2 (Kamenos et al, 2013(Kamenos et al, , 2016Hennige et al, 2015;Pauly et al, 2015). These changes potentially reflect differences in calcifying fluid carbonate chemistry.…”
mentioning
confidence: 99%
“…Manuscript to be reviewed physiological advantage or higher stress resistance of the orange colourmorph of L. pertusa. At least with regard to framework formation, colour variation does not seem to have adverse impacts on the reef development, as it was recently shown that self-recognition even between genetically distinct colonies of these two colour variants can lead to skeletal fusion (Hennige et al, 2014b). The similar skeletal densities of white and orange corals as observed here thereby probably facilitate skeletal fusion.…”
Section: White Vs Orange Colourmorphssupporting
confidence: 68%
“…We collected 440 spectra from various grains spread onto a glass slide. Although JCp-1 exists in ground form, we note that analysis of intact coral skeletons is also possible (Wall and Nehrke, 2012;Hennige et al, 2014) and that peak widths apparently do not depend on whether the sample is ground or intact (Zakaria et al, 2008), as long as the grain size exceeds the laser spot size.…”
Section: Raman Measurementsmentioning
confidence: 83%